Perfil da imunoexpressão de receptores opioides em lesões potencialmente malignas e no carcinoma de células escamosas de boca e orofaringe e correlação clínico-patológica com marcadores de proliferação e morte celular - Dantas, Thinali Sousa (2021)
Squamous Cell Carcinoma (SCC) accounts for approximately 95% of all oral and oropharyngeal malignancies. The prognosis of this tumor is stage dependent. More advanced stages result in shorter patient survival as well as greater suffering, which can be minimized with opioid analgesics. Although the effects of these drugs on the central nervous system are well established, little is known about their action on tumor cells. Therefore, the aim of this retrospective study, divided in two chapters, was to characterize the immunoexpression profile of Mu (μ) (MOR), Kappa (κ) (KOR) opioid receptors in oral mucosa epithelium (OME), oral potentially malignant lesions (OPML), and oral and oropharyngeal squamous cell carcinoma (OOSCC), as well as to correlate these immunoexpression findings with prognostic factors, proliferation, and cell death markers. In Chapter 1, we analyzed 25 OME samples and 25 OPML samples with dysplasia and 50 oral SCC samples from the Cancer Institute of Ceará (CIC) by immunohistochemistry for Mu opioid, Kappa opioid and Ki67 receptors. In Chapter 2, 50 patients with oropharyngeal SCC treated at the CIC were evaluated by immunohistochemistry for Mu opioid, Kappa opioid, Ki67 and caspase-3 receptors. In both chapters, sociodemographic and clinicopathological data were collected. The percentage of epithelial cells exhibiting immunostaining was evaluated with the ImageJ software in association with clinical-pathological and prognostic data. The data were analyzed with Mann-Whitney, Kruskal-Wallis / Dunn tests, Spearman correlation, Log-Rank Mantel-Cox, and Cox regression. In Chapter 1, oral samples showed increased immunoexpression of both opioid receptors in OPML and OOSC compared to OME, mainly in the nucleus, cytoplasm, and perinuclear membrane. For the Ki67 it was considered nuclear marking. Clinical characteristics such as sex, age, smoking history, alcohol consumption, and location of the primary tumor did not influence the immunoexpression of opioid receptors. A lower expression of MOR was observed in T1 tumors, whereas a greater immunoexpression of cytoplasmic KOR was observed in deceased patients. In Chapter 2, in the oropharynx, the immunoexpression of MOR, KOR, Ki67, and caspase-3 were significantly higher in primary tumors and lymph node metastases from p16 + and p16-tumors compared to surgical margins. It was observed that the lower expression of caspase 3 negatively influenced the survival of patients, and, in multivariate analysis, nuclear expression of MOR was directly associated with lower risk of death, whereas nuclear expression of KOR was associated with a higher risk. Thus, it appears that opioid receptors are directly related to the carcinogenesis and the prognosis of OOSCC; however, the mechanisms by which these receptors affect tumor cell proliferation and death remain unclear.